ANALYZING THE SOCIO-ECONOMIC CONSEQUENCES OF THE PARTITION OF BENGAL (1905–1911): A REASSESSMENT OF NATIONALIST STRATEGIES AND BRITISH IMPERIAL TACTICS - Siva Nath Pait (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The partition of Bengal in 1905 was a pivotal event in Indian history that had far-reaching socio-economic consequences. The British colonial administration’s decision to divide Bengal into two provinces was ostensibly made to improve administrative efficiency, but it was largely seen as a tactic to weaken the growing nationalist movement by creating divisions between Hindus and Muslims. It had depth socio-economic Consequences. The colonial economy marginalized local industries and artisans, leading to widespread discontent and fuelling nationalist sentiments. A resurgence in cultural pride and identity among Bengalis fuelled nationalist sentiments, with a focus on promoting Bengali literature, art, and traditions. The British exploited religious differences, leading to increased hostility between Hindus and Muslims and creating long-term social fragmentation. The partition galvanized nationalist movements, including the Swadeshi Movement, which advocated for Indian-made goods and self-reliance.